OPPORTUNITIES FOR UTILIZING OPEN EDUCATIONAL RESOURCES IN PHYSICS TEACHING (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
This paper explores the transformative potential of Open Educational Resources (OER) in physics education, emphasizing their role in enhancing accessibility, engagement, and inclusivity. As traditional educational materials become increasingly costly, OER offers a sustainable and equitable alternative, providing free and adaptable resources that support diverse learning needs. The study highlights how OER can improve students’ understanding of complex physics concepts, such as quantum mechanics, through interactive and collaborative digital tools. Furthermore, it discusses the capacity of OER to address educational disparities by fostering equal learning opportunities for underrepresented student groups. The integration of active learning strategies and technology-enhanced collaboration—such as the Peripatetic Electronic Teacher (PET) model—is also examined. The paper concludes that OER not only enriches the teaching and learning experience but also holds significant promise for reshaping physics education in line with modern pedagogical standards.